HOTEL SYARIAH DALAM TEORI DAN PRAKTIKNYA DI INDONESIA - Muhammad Rayhan Janitra; Misno; Dodi Yarli (JURNAL ALAMIAH, 2022)
Nowadays, Sharia Hotel becomes pertinent issue amid remarkable growth of shariah tourism across the globe. This implies that hospitality need that comply to the tenet of shariah is imperative issue to decipher its potential. This paper aims to explore regulatory framework of this business and unveil its shariah dimension from proper pedigree of Shariah tourism as well as shariah perspective. This paper employs qualitative descriptive approach where semi structured interview is undertaken to strengthen the analysis. Furthermore, this paper benchmarks Islamic legal sources to examine its accuracy with hotel operation that in line with shariah principles. The finding of this paper reveals that there are seven dimensions of hotel to become shariah hotel as follow: hotel facilities, beverage, staff, guest, financial management, and corporate governance of hotel. This paper concludes that Islam regulates six principles on hotel business that should be appropriate with the principle of consumption, entertainment, business activities, ethic and dress, some restriction on external relations, and layout. The finding implies that these principles have to be taken into account by hotel management using sharia system in order to make it truly sharia.